Discovery of Mycothiogranaticins from Streptomyces vietnamensis GIMV4.0001 and the Regulatory Effect of Mycothiol on the Granaticin Biosynthesis - Deng, Ming-Rong; Li, Yan; Luo, Xiao; Zheng, Xiang-Ling; Chen, Yuchan; Zhang, Yu-Lian; Zhang, Weimin; Zhou, Hao; Zhu, Honghui (Frontiers in Chemistry, 2021)
Granaticins are benzoisochromanequinone polyketides with remarkable antibacterial and anticancer activities. Three sulfur-containing granaticin congeners, mycothiogranaticins A (1), B (2) and granaticin MA (3) were discovered from a granaticin-producing strain of Streptomyces vietnamensis GIMV4.0001. Two of them were structurally determined with mycothiol or N-acetylcysteine moieties and found to be bio-actively reluctant. Disruption of the mshA gene (SVTN_RS20640) that encodes the D-inositol-3-phosphate glycosyltransferase crucial for mycothiol biosynthesis, fully abolished the production of mycothiogranaticins. The result substantiated that the newly discovered mycothiogranaticins are consequences of the combination of the granaticin and mycothiol biosynthetic pathways. The overall granaticin production of the ΔmshA mutant strain was unexpectedly decreased by at least more than 50%, while similar production level of granaticins to that of the wild type strain was observed in an mycothiol-S transferase gene (SVTN_RS22215) disruptant Δmst. These results indicated that the mycothiol deficiency was responsible for the decreased production of granaticins. Mycothiol may positively regulate the biosynthesis of granaticin possibly by maintaining the cellular redox balance. To the best of our knowledge, this is the first report that mycothiol can not only be a direct building block of polyketides but also play a regulatory role in the polyketide biosynthesis.